2011
DOI: 10.1007/s10924-011-0362-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties and Biodegradability Studies of Poly(3-hydroxybutyrate-co-3-hydroxyvalerate)

Abstract: For investigating the relationship between thermal properties and biodegradability of poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), several films of PHBV containing different polyhydroxyvalerate (HV) fractions were subjected to degradation in different conditions for up to 49 days. Differential scanning calorimetry (DSC), thermogravimetry (TG), specimen weight loss and scanning electron microscopy (SEM) were performed to characterize the thermal properties and enzymatic biodegradability of PHBV. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 26 publications
(33 reference statements)
4
34
0
3
Order By: Relevance
“…Increasing PHB surface area and porosity increases the available binding sites for biological enzymatic degradation and may therefore increase hydrolysis rates (Shang et al, 2012). Hydrolysis of recalcitrant substrates can be the rate-limiting step in methanogensis, thus pretreatments that can facilitate increased rates of hydrolysis may increase the rate of methanogenesis (Venkiteshwaran et al, 2015).…”
Section: Bioplastic Pretreatment and Bmp Assaysmentioning
confidence: 99%
“…Increasing PHB surface area and porosity increases the available binding sites for biological enzymatic degradation and may therefore increase hydrolysis rates (Shang et al, 2012). Hydrolysis of recalcitrant substrates can be the rate-limiting step in methanogensis, thus pretreatments that can facilitate increased rates of hydrolysis may increase the rate of methanogenesis (Venkiteshwaran et al, 2015).…”
Section: Bioplastic Pretreatment and Bmp Assaysmentioning
confidence: 99%
“…Petroleum-based non-biodegradable synthetic plastics are cheap and convenient [1]; however, their universal use has brought great damage to the environment and ecological systems because of poor biodegradability [2][3][4]. The development of biodegradable plastics is regarded as an effective way to solve the increasingly serious environmental crisis caused by the use of non-biodegradable synthetic plastics [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Methane based production of degradable bioplastics-polyhydroxybutyrate (PHB) and its copolymer with valerate (PHB/V)-is promising for the biodegradable packaging of drugs and food products in biomedicine and for the encap sulation of agrochemicals in agriculture [28]. Screen ing has shown that methanotrophs with the serine С 1 metabolism accumulate large amounts of the biopoly mer [29].…”
mentioning
confidence: 99%